Utility of Gastric Aspirates in Screening for Pulmonary Tuberculosis in High Risk Subjects: The Manitoba Experience - A Bahammam; SH Choudhri; R Long (Canadian Journal of Infectious Diseases)
BACKGROUND: Although gastric aspirates (GA) are one of the recommended screening procedures for asymptomatic individuals at high risk for developing tuberculosis (TB), little data exist on the utility of GA for this indication.